2011
DOI: 10.1161/circulationaha.111.037036
|View full text |Cite
|
Sign up to set email alerts
|

Average Daily Blood Pressure, Not Office Blood Pressure, Is Associated With Progression of Cerebrovascular Disease and Cognitive Decline in Older People

Abstract: Background High blood pressure (BP) is a risk factor for cerebrovascular disease, including stroke. Little is known about the importance of BP on the progression of microvascular disease of the brain that has been associated with functional decline in mobility and cognition in older people. Methods and Results This was a prospective cohort of subjects 75-89 years to determine relations among vascular risk factors, white matter hyperintensity volume (WMHs), and functional status. 99 subjects were enrolled usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
97
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 33 publications
0
97
1
3
Order By: Relevance
“…Approximately two-thirds of individuals over 75 years of age have detectable WMHs using MRI of the brain. 54 The lower limit of detection of WMH by experts in neuroradiology is approximately 0.2 to 0.3% of intracranial contents, and 0.5% is easily visible to the naked eye based on our experience. 8,54,65 Our cohort studies have demonstrated an increase of WMH volume from 0.99 to 1.47 to 1.7% of the intracranial contents volume from baseline to 2 and 4 years respectively.…”
Section: 58mentioning
confidence: 72%
See 4 more Smart Citations
“…Approximately two-thirds of individuals over 75 years of age have detectable WMHs using MRI of the brain. 54 The lower limit of detection of WMH by experts in neuroradiology is approximately 0.2 to 0.3% of intracranial contents, and 0.5% is easily visible to the naked eye based on our experience. 8,54,65 Our cohort studies have demonstrated an increase of WMH volume from 0.99 to 1.47 to 1.7% of the intracranial contents volume from baseline to 2 and 4 years respectively.…”
Section: 58mentioning
confidence: 72%
“…54 The lower limit of detection of WMH by experts in neuroradiology is approximately 0.2 to 0.3% of intracranial contents, and 0.5% is easily visible to the naked eye based on our experience. 8,54,65 Our cohort studies have demonstrated an increase of WMH volume from 0.99 to 1.47 to 1.7% of the intracranial contents volume from baseline to 2 and 4 years respectively. 8,54 This increase was even present in participants with normal mobility throughout the study period.…”
Section: 58mentioning
confidence: 72%
See 3 more Smart Citations